PENGARUH PENERAPAN STRATEGI PEMECAHAN MASALAH DALAM PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SHARE (TPS) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VII SMP NEGERI 25 PEKANBARU - Aini, Zahratul; Saragih, Sehatta; Suhermi, Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research aims to determine the influence of the implementation of problem solving strategy in TPS structural approach of cooperatif learning to the mathematical problem solving ability of students. This research was conducted in SMP Negeri 25 Pekanbaru on odd semester academic year 2017/2018. This is a pre-experimental research which using the static-group comparison design. The population is all of students at grade VII in SMP Negeri 25 Pekanbaru. The sample in this research consists of two class, where the VII8 as an experimental class and the VII9 as a control class. Class experimental was implemented the problem solving strategy in TPS structural approach of cooperative learning and class control class was implemented TPS structural approach of cooperative learning. The instrument of collecting data in this research is early mathematical ability test and mathematical problem solving ability test (postest). The postest result was analyzed by parametric statistic test of Independent Sample T-test and the magnitude of the influence was calculated using the Cohen’s formula. The result of the research showed that implementation of problem solving strategy in TPS structural approach of cooperatif learning gave the positive effect to the mathematical problem solving ability students. The implementation of problem solving strategy in TPS structural approach of cooperatif learning had a magnitude of the effect for 79% toward mathematical problem solving ability the students of class SMP Negeri 25 Pekanbaru and included in the large category.Key Words : Problem solving strategy, Think Pair Share structural approach to cooperatifLeraning, mathematical problem solving ability